2020
DOI: 10.1098/rsta.2019.0294
|View full text |Cite
|
Sign up to set email alerts
|

Fractional-order nonlinear hereditariness of tendons and ligaments of the human knee

Abstract: In this paper the authors introduce a nonlinear model of fractional-order hereditariness used to capture experimental data obtained on human tendons of the knee. Creep and relaxation data on fibrous tissues have been obtained and fitted with logarithmic relations that correspond to power-laws with nonlinear dependence of the coefficients. The use of a proper nonlinear transform allows one to use Boltzmann superposition in the transformed variables yielding a fractional-order model for the nonlinear mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Third, the authors characterize the mechanical characteristics of the meniscus as the isotropic single-phase linear elastic material. It is prospected to consider the viscoelasticity of the tissue in the future work [42][43][44]. Hence, future studies with an improved design and…”
Section: Fatigue Analysis Results Of Meniscus Modelmentioning
confidence: 99%
“…Third, the authors characterize the mechanical characteristics of the meniscus as the isotropic single-phase linear elastic material. It is prospected to consider the viscoelasticity of the tissue in the future work [42][43][44]. Hence, future studies with an improved design and…”
Section: Fatigue Analysis Results Of Meniscus Modelmentioning
confidence: 99%
“…The approach is readily implementable in numerical form to calculate either stress or strain responses of any fractional system where fractional order may change with time. Finally, Bologna et al [55] propose a nonlinear extension of fractional calculus to tissue biomechanics, in order to handle the time-dependent mechanics of ligaments and tendons of the human knee. The authors point out that fibrous tissues exhibit a marked nonlinear behaviour in terms of relaxation and creep functions with coefficients and orders depending nonlinearly on applied strain and stress, respectively.…”
Section: Materials Hereditariness: Viscoelasticitymentioning
confidence: 99%
“…The theme issue includes several contributions on linear and nonlinear fractional viscoelasticity, as applied to various types of materials [50][51][52][53][54][55]. Atanackovic et al [50] investigate the thermo-dynamical restrictions on constitutive equations for viscoelastic fluids, as following from a weak form of entropy inequality under isothermal conditions.…”
Section: Materials Hereditariness: Viscoelasticitymentioning
confidence: 99%
“…However, investigation of the hereditariness of musculoskeletal tissues subverted the above assumptions. For example, self-similar fractals [24] emerge from the micro–nano structures of ligaments and tendons, and their time-dependent viscoelasticity can be described using fractional-order derivatives [5]. Guo et al [6] further showed a relationship between fractional-order viscoelasticity and self-similar micro–nano structures.…”
Section: Introductionmentioning
confidence: 99%